Design advanced perspectives of Darcy-Forchheimer flow of thermophoretic particle deposition in hybrid nanofluid capturing thermal radiation and Soret-Dufour effects - Abbas, Munawar; Khan, Nargis; Salleh, Zabidin; Hashmi, M. S.; Rezapour, Shahram; İnç, Mustafa (Elsevier, 2025)
Background: To evaluate the properties of Soret and Dufour effect on thermophoresis particle deposition in Darcy-Forchheimer flow of HNF (hybrid nanofluid) across over plate, wedge, and cone with Marangoni convection effects. Furthermore, Joule heating and mixed convection influence are considered. The properties of the HNF model are claimed by combining titanium dioxide (TiO2) and iron oxide (Fe3O4) particles with water (H2O) as improper liquid. Methods: A suitable similarity variable can be used to convert the constitutive PDEs into a system of non-linear ODEs. The following equations are then solved systematically using the effective HAM (Homotopy analysis method). Applications: The proposed model has significant uses in improving thermal performance in a variety of industrial systems, including heat exchangers, solar energy collectors and electronic device cooling. The model offers information on improving heat and mass transport by combining MC (Marangoni convection), Soret-Dufour effects, thermophoretic particle deposition, HNF in porous media. This is especially helpful for sectors like chemical processing, nuclear reactors, and microfluidic devices where accurate thermal control and effective energy consumption are essential. Improved thermal conductivity and system dependability are further benefits of integrating HNF. Results: Graphs are used to analyze the key factors that influence the flow, thermal and solutal profiles. With higher values for the magnetic and Forchheimer parameters, the velocity profile drops. The thermophoretic parameter causes the solutal profile to decrease. The velocity distribution is enhanced with a rise in the MC parameter, but the conduct of the thermal and concentration distribution is inverse.
Keywords: Marangoni convection; Homotopy analysis method (HAM); Hybrid nanofluid; Darcy-Forchheimer flow; Thermophoretic particle deposition; Soret and Dufour effects